Censorship: Grindr (Oman) - Voidly (Voidly Global Censorship Index, 2024)
WARNING severity censorship detected in Oman. Data sourced from CensoredPlanet.
Censorship Incident ID: OM-2024-0001. Severity: warning. Confidence: 75%